Galaxy and Mass Assembly (GAMA). The Properties of Quasar Host Galaxies: Star Formation Histories and Stellar Populations - Stone, Maria B.; De Propris, Roberto; Wethers, Clare; Kotilainen, Jari; Acharya, Nischal; Holwerda, Benne; Hopkins, Andrew M.; Pimbblet, Kevin (Institute of Physics Publishing, 2026)
We investigated the star formation history and stellar populations of a sample of 205 Type I quasar host galaxies (0.1 < z < 0.35) and compared them with normal (nonactive) galaxies of the same mass and redshift within the volume of the Galaxy and Mass Assembly redshift survey. We find that quasar host galaxies tend to be star-forming galaxies (∼80%) lying on the star-forming main sequence; the fraction of quasar host galaxies that are quiescent (∼20%) is lower than the fraction of quiescent galaxies in the comparison sample of normal galaxies (54%). We find that the mean star formation rate (SFR) of quasar host galaxies has increased over the past 100 Myr by a factor of 2–3, but these galaxies were star-forming at all times previously. Our data are more consistent with quasar activity originating together with an increase in the SFR of otherwise normal galaxies, similar to episodic star formation in normal spirals. We argue that this indicates that secular processes and minor mergers may be the favored triggers of nuclear activity in the local Universe.